2014
DOI: 10.1542/peds.2013-1379
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Effects of Sleep Duration on Blood Pressure

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Inconsistent results have been reported on the association between sleep duration and blood pressure (BP) in children, likely as a result of inadequate adjustment for confounders and the use of different time frames in assessing sleep duration.WHAT THIS STUDY ADDS: Short sleep duration and poor sleep quality are associated with higher BP in normal-weight adolescents. One night of adequate sleep may partially ameliorate the risk of high BP but cannot completely reverse the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 39 publications
0
26
0
5
Order By: Relevance
“…Three of these reported that decreased sleep duration or decreased sleep continuity was associated with elevated BP for a portion or all of the ambulatory monitoring period. 43;45;46 In contrast, Martikainen et al reported that neither self-reported sleep disturbance nor actigraphy-assessed sleep characteristics were associated with ambulatory BP in a sample of Finnish 8-year-olds. 50;55 Thus, it is possible that multiple measurements of BP collected over an extended time period may reveal more robust associations with sleep than a limited number of clinic assessments.…”
Section: Resultsmentioning
confidence: 93%
“…Three of these reported that decreased sleep duration or decreased sleep continuity was associated with elevated BP for a portion or all of the ambulatory monitoring period. 43;45;46 In contrast, Martikainen et al reported that neither self-reported sleep disturbance nor actigraphy-assessed sleep characteristics were associated with ambulatory BP in a sample of Finnish 8-year-olds. 50;55 Thus, it is possible that multiple measurements of BP collected over an extended time period may reveal more robust associations with sleep than a limited number of clinic assessments.…”
Section: Resultsmentioning
confidence: 93%
“…For example, an increase in body weight [50], a higher risk of obesity [51][52][53], and a reduced physical activity [54] in association with low sleep were observed in the teen population. Furthermore, sleep loss in adolescents is likely to lead to increases in blood pressure [55,56] and high cardiometabolic risk [57]. Poor sleep in adolescents is also positively associated with other somatic outcomes, such as headache [58], persistent fatigue [59], and lower back, neck, and abdominal pain [60].…”
Section: The Effects Of Sleep Deprivation On Health Performance Andmentioning
confidence: 99%
“…4,5 Sleep deprivation is associated with daytime sleepiness, attention impairment, and poor academic performance, [6][7][8][9] and it is also empirically linked to heightened risk of mood disorders, obesity, hyperlipidemia, and high blood pressure in young students. [10][11][12][13][14] An interactive network of internal and external factors contributes to insufficient sleep in adolescents. Although adolescents experience a marked change in circadian timing with a consequent delay of bedtime, 15 school start time, academic work, extracurricular activities, media usage, and parental sleep pattern can all impede their sleep-wake schedule.…”
Section: What This Study Addsmentioning
confidence: 99%